Metabolic and hormonal responses to acute high-load resistance exercise in normobaric hypoxia using a saturation clamp - Jiang, Guole; Qin, Shuang; Yan, Bing; Girard, Olivier (Frontiers in Physiology, 2024)
We assessed metabolic and hormonal responses to high-load resistance exercise under varying normobaric hypoxia conditions with a saturation clamp. Employing a counterbalanced, crossover test design, ten well-trained men participated in three exercise trials with normoxic or hypoxic gas mixtures to maintain arterial oxygen saturation at ~90% and 80% [moderate (MH) and severe (SH) hypoxia, respectively]. The resistance exercise regimen comprised five sets of 10 repetitions of barbell back squats at 70% of one repetition maximum, with one-minute rest between sets. Metabolic and hormonal responses were measured before normoxia or hypoxia exposures (Pre 1), 15 minutes after the exposures (Pre 2), and at 0-, 15-, and 30-minutes post-exercises (T0, T15 and T30, respectively). Compared to Pre 2, blood lactate concentrations and growth hormone values were elevated at T0, T15, and T30 (P≤0.001), while testosterone values increased at T0 in all conditions (P≤0.009). Epinephrine values increased significantly from Pre 2 to T0 in SH only (P<0.001). SH had significantly higher blood lactate concentrations (P=0.023), growth hormone (P=0.050), and epinephrine (P=0.020) values at T30 compared to NM. Cortisol values were elevated above Pre 2 at T15 in MH and SH, while lower testosterone values were noted at T0 and T15 for SH compared to NM and MH (all P≤0.05). Severe simulated hypoxia, achieved through a saturation clamp during barbell back squats, may enhance metabolic and hormonal responses, particularly 30 minutes postsession. Nevertheless, the acute effects of hypoxia exposure seem to be overridden by the impact of high-load resistance exercise.